Tax Avoidance in Manufacturing: Profitability, Leverage, Ownership, Size, and Age Impact: Avoidansi Pajak di Manufaktur: Profitabilitas, Leverage, Kepemilikan Institusional, Ukuran, dan Usia Perusahaan - Fitri Alfia Anggraini; Herman Ernandi (Academia Open, 2024)
This study aims to determine whether profitability, leverage, institutional ownership, firm size and firm age have an effect on Tax Avoidance. profitability, leverage, institutional ownership, company size and company age have an effect on Tax Avoidance in consumer goods manufacturing companies listed on the Indonesia Stock Exchange in 2014 – 2017. The population in this study are manufacturing companies in the consumer goods industry sector which are actively traded and listed on the Indonesian Stock Exchange. Indonesia Stock Exchange 2014-2017 period. The research sample was taken using purposive sampling method which used multiple regression analysis with panel data approach. There are 8 companies used in the research sample. From the analysis of the results of the R test, it can be concluded that the R Square value is 0.769, this means that the influence of profitability, leverage, institutional ownership, company size and company age simultaneously influence tax avoidance by 76%. Highlights: Comprehensive Analysis: The study provides a thorough examination of key factors—profitability, leverage, institutional ownership, company size, and age—in relation to tax avoidance, offering a holistic view of their combined impact. Significant Influence: With a robust R Square value of 0.769, the research underscores the substantial influence of the specified factors, collectively explaining 76% of the variance in tax avoidance among consumer goods manufacturing companies in Indonesia. Methodological Precision: Employing a purposive sampling method and a panel data approach with multiple regression analysis, the study ensures a methodologically sound exploration of the chosen companies within the specified timeframe on the Indonesia Stock Exchange. Keywords: Profitability, Leverage, Institutional ownership, Company size, Company age, Tax avoidance